1992
DOI: 10.1073/pnas.89.19.9131
|View full text |Cite
|
Sign up to set email alerts
|

Expression of myosin-class II major histocompatibility complexes in the normal myocardium occurs before induction of autoimmune myocarditis.

Abstract: Determining how an autoimmune response is initiated is essential to understanding the mechanisms of autoimmunity. Self-reactive T cells, self-protein, and a failure of tolerance to that self-protein are all involved in the pathogenesis of autoimmune disease; yet it is not clear how self-reactive T cells rind the target self-protein to initiate an autoimmune response. Although a variety of self-proteins have been shown to be presented on both class I and class II major histocompatibility complex (MHC) molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 46 publications
5
84
0
3
Order By: Relevance
“…In vitro spontaneous T cell response to cardiac myosin and derived-peptide could be blocked by anti-DQ antibody thus suggesting it to be DQ-specific. Cardiac myosin MHC class II complexes have been shown to be constitutively expressed on cardiac APCs [27]. There was a marked increase in the expression of DQ8 in these mice similar to what is known from biopsies of myocarditis patients [28].…”
Section: Discussionsupporting
confidence: 58%
“…In vitro spontaneous T cell response to cardiac myosin and derived-peptide could be blocked by anti-DQ antibody thus suggesting it to be DQ-specific. Cardiac myosin MHC class II complexes have been shown to be constitutively expressed on cardiac APCs [27]. There was a marked increase in the expression of DQ8 in these mice similar to what is known from biopsies of myocarditis patients [28].…”
Section: Discussionsupporting
confidence: 58%
“…2A). This MHCII expression appears to be on cardiac professional APCs, mainly macrophages and DCs, which are present in significant numbers in the heart under steady-state conditions [9,27]. Costaining of MHCII molecules with the endothelial cell marker CD31 reveals that mainly endothelial cells of the interstitial capillary network upregulate MHCII expression in inflamed hearts ( Fig.…”
Section: Endothelial Mhcii Expression Is Induced During Eammentioning
confidence: 92%
“…MHCII is primarily expressed on professional APCs. Cardiac APCs were suggested to present cardiac myosin before the onset of cardiac pathology [9], and DCs, the major APC subset able to initiate primary immune responses, were shown to be critical for disease induction [5,10]. However, MHCII molecules are also upregulated on nonhematopoietic cells under inflammatory conditions [11,12].…”
mentioning
confidence: 99%
“…62 Evidence has shown that in normal myocardium myosin-class II major histocompatibility antigen complexes are present before the induction of autoimmune myocarditis. 63 Induction of myocarditis is seen only with cardiac myosin and not skeletal myosin 23 or other ␣-helical coiled-coil proteins such as tropomyosin (Galvin and Cunningham, unpublished data). Streptococcal M protein mimics cardiac myosin sequences or epitopes and immunization with the M protein or peptides leads to myocardial and valvular inflammatory heart lesions in BALB/c mice and Lewis rats.…”
Section: Susceptibilty To Myocarditis In Rodent Modelsmentioning
confidence: 99%